{-# OPTIONS --without-K --safe #-}
module Function.HalfAdjointEquivalence where
open import Function.Base
open import Function.Equality using (_⟨$⟩_)
open import Function.Inverse as Inv using (_↔_; module Inverse)
open import Level
open import Relation.Binary.PropositionalEquality
record _≃_ {a b} (A : Set a) (B : Set b) : Set (a ⊔ b) where
field
to : A → B
from : B → A
left-inverse-of : ∀ x → from (to x) ≡ x
right-inverse-of : ∀ x → to (from x) ≡ x
left-right :
∀ x → cong to (left-inverse-of x) ≡ right-inverse-of (to x)
inverse : A ↔ B
inverse = Inv.inverse to from left-inverse-of right-inverse-of
injective : ∀ {x y} → to x ≡ to y → x ≡ y
injective {x} {y} to-x≡to-y =
x ≡⟨ sym (left-inverse-of _) ⟩
from (to x) ≡⟨ cong from to-x≡to-y ⟩
from (to y) ≡⟨ left-inverse-of _ ⟩
y ∎
where
open ≡-Reasoning
↔→≃ : ∀ {a b} {A : Set a} {B : Set b} → A ↔ B → A ≃ B
↔→≃ A↔B = record
{ to = to ⟨$⟩_
; from = from ⟨$⟩_
; left-inverse-of = left-inverse-of
; right-inverse-of = right-inverse-of
; left-right = left-right
}
where
open ≡-Reasoning
open module A↔B = Inverse A↔B using (to; from; left-inverse-of)
right-inverse-of : ∀ x → to ⟨$⟩ (from ⟨$⟩ x) ≡ x
right-inverse-of x =
to ⟨$⟩ (from ⟨$⟩ x) ≡⟨ sym (A↔B.right-inverse-of _) ⟩
to ⟨$⟩ (from ⟨$⟩ (to ⟨$⟩ (from ⟨$⟩ x))) ≡⟨ cong (to ⟨$⟩_) (left-inverse-of _) ⟩
to ⟨$⟩ (from ⟨$⟩ x) ≡⟨ A↔B.right-inverse-of _ ⟩
x ∎
left-right :
∀ x →
cong (to ⟨$⟩_) (left-inverse-of x) ≡ right-inverse-of (to ⟨$⟩ x)
left-right x =
cong (to ⟨$⟩_) (left-inverse-of x) ≡⟨⟩
trans refl (cong (to ⟨$⟩_) (left-inverse-of _)) ≡⟨ cong (λ p → trans p (cong (to ⟨$⟩_) _))
(sym (trans-symˡ (A↔B.right-inverse-of _))) ⟩
trans (trans (sym (A↔B.right-inverse-of _))
(A↔B.right-inverse-of _))
(cong (to ⟨$⟩_) (left-inverse-of _)) ≡⟨ trans-assoc (sym (A↔B.right-inverse-of _)) ⟩
trans (sym (A↔B.right-inverse-of _))
(trans (A↔B.right-inverse-of _)
(cong (to ⟨$⟩_) (left-inverse-of _))) ≡⟨ cong (trans (sym (A↔B.right-inverse-of _))) lemma ⟩
trans (sym (A↔B.right-inverse-of _))
(trans (cong (to ⟨$⟩_) (left-inverse-of _))
(trans (A↔B.right-inverse-of _) refl)) ≡⟨⟩
right-inverse-of (to ⟨$⟩ x) ∎
where
lemma =
trans (A↔B.right-inverse-of _)
(cong (to ⟨$⟩_) (left-inverse-of _)) ≡⟨ cong (trans (A↔B.right-inverse-of _)) (sym (cong-id _)) ⟩
trans (A↔B.right-inverse-of _)
(cong id (cong (to ⟨$⟩_) (left-inverse-of _))) ≡⟨ sym (naturality A↔B.right-inverse-of) ⟩
trans (cong ((to ⟨$⟩_) ∘ (from ⟨$⟩_))
(cong (to ⟨$⟩_) (left-inverse-of _)))
(A↔B.right-inverse-of _) ≡⟨ cong (λ p → trans p (A↔B.right-inverse-of _))
(sym (cong-∘ _)) ⟩
trans (cong ((to ⟨$⟩_) ∘ (from ⟨$⟩_) ∘ (to ⟨$⟩_))
(left-inverse-of _))
(A↔B.right-inverse-of _) ≡⟨ cong (λ p → trans p (A↔B.right-inverse-of _))
(cong-∘ _) ⟩
trans (cong (to ⟨$⟩_)
(cong ((from ⟨$⟩_) ∘ (to ⟨$⟩_))
(left-inverse-of _)))
(A↔B.right-inverse-of _) ≡⟨ cong (λ p → trans (cong (to ⟨$⟩_) p) _)
(cong-≡id left-inverse-of) ⟩
trans (cong (to ⟨$⟩_) (left-inverse-of _))
(A↔B.right-inverse-of _) ≡⟨ cong (trans (cong (to ⟨$⟩_) (left-inverse-of _)))
(sym (trans-reflʳ _)) ⟩
trans (cong (to ⟨$⟩_) (left-inverse-of _))
(trans (A↔B.right-inverse-of _) refl) ∎